Biocatalytic synthesis of polymeric esters used as emulsifiers - Ortega-Requena, Salvadora (Array, 2019)
Polyglycerol polyricinoleate (PGPR) is a polymeric ester widely used as emulsifier in the food industry. In this work, PGPR biocatalytic synthesis was carried out in a onestep solvent-free enzymatic process using lipase CALB immobilized in Lewatit® Monoplus MP 64 by adsorption. The optimal immobilization conditions were determined: initial enzyme concentration of 13 mg of Lowry protein per mL phosphate buffer pH 7, and ricinoleic acid as a support activator. An immobilized derivative with 35.93 ± 4.90 mg of Lowry protein per g of dry support was obtained. It was used as a catalyst for PGPR production in open air and vacuum batch reactors, and the results obtained showed that only when the reaction equilibrium was shifted towards ester production by means of water removal, the PGPR produced fulfilled the European legislation (acid value ≤ 6 mg of KOH per g of product).